Analysis and optimization of digital agency project activities - Olga Yu. Basharina; Tatiana V. Fer; Irina S. Shilnikova (Цифровые модели и решения)
The article deals with modelling the project activity of a digital agency in or der to increase the efficiency of its business processes. In accordance with the modelling methodology, the paper develops a multi-level business process model using IDEF0 and BPMN notations in a specialised Business Studio software environment. The assessment and analysis of the current activity model, carried out using SWOT analysis, visualisation and problem identification methods, identify the main weaknesses and potential opportu nities of business processes. The reorganisation of business processes inherent in the target model allows for a significant reduction in the development time of advertising projects for digital agency clients. Using a centralised data warehouse in the project accounting system eliminates information redundancy, reduces time for data entry and processing, and min imises the probability of errors. The proposed optimisation measures do not require large f inancial expenses and radical changes in the structure of the agency and business processes.